Straight-time and Overtime: A Sequential-Lottery Approach - Aleksandar Vasilev (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This note explores the problem of aggregation with non-convex labor supply decisions in an economy with both straight time and overtime. In contrast to Hansen and Sargent (1988), the paper models this as a sequential decision. Instead of changing from one to infinity, with a sequential non-convexity, the aggregate elasticity of labor supply for overtime work is a function of overall participation rate, and the aggregate elasticity of labor supply for full-time work depends on the share of workers doing overtime.
Keywords: J2; E13; 330; straight time; overtime; indivisible labor; sequential lottery